The Effect of Audiobook Media on Students’ Listening Comprehension at Tenth Grade of SMA Negeri 2 Tarakan - Ramli, Ramli; Kusmaryani, Woro; Daniel, Agustinus (Universitas Muhammadiyah Mataram, 2025)
This research was aimed to investigate the impact of audiobooks on the listening comprehension of students in the English language study at SMA Negeri 2 Tarakan. This investigation employed a pre-experimental design. The researcher collected data from a single class, X-F, composed of 35 students. A written listening test was implemented. The results indicated that the students’ score prior to treatment was 53.91, increasing to 77.60 following the treatment. Consequently, Ha was accepted, and Ho was rejected. The findings demonstrated that audiobooks have the potential to significantly enhance students’ listening comprehension. This media offered advantages in consistent speaking speed, correct pronunciation, and intonation, as well as more comprehensive comprehension of context and details in identifying information from descriptive, narrative, and recount contexts. Therefore, audiobooks can be a highly effective tool for enhancing listening abilities, particularly in the context of language education, during the teaching and learning process.